T cell epitope specificity in human allergic and nonallergic subjects to bee venom phospholipase A2 - Carballido, JM; Carballido-Perrig, N; Kagi, MK; Meloen, RH; Wuthrich, B; Heusser, CH; Blaser, K (The Journal of immunology (1950), 1993)
Phospholipase A2 (PLA) is a biochemically fully defined glycoprotein, representing the main allergen of bee venom. We have established CD4+ T cell clones specific to PLA from subjects allergic and nonallergic to bee sting. By screening the epitope specificity of these clones with 62 synthetic overlapping dodecapeptides representing the PLA molecule, two immunogenic epitopes, PLA81-92 and PLA113-124, were identified. Additional screening, using longer peptides of up to 18 residues, revealed a third epitope at position PLA 45-62. These epitopes are recognized by specific T cell clones in association with HLA-DP and -DQ molecules, although HLA-DR-associated responses to PLA exist. Primary in vitro proliferation of unfractionated PBMC from bee sting allergic, hyposensitized, or hyperimmune subjects to PLA-derived peptides revealed the same immunogenic sites as found in the T cell clones. Among the different groups of individuals, proliferative responses to the PLA molecule and fragments thereof were generally higher in allergic patients than in nonallergic subjects. Thus, at least three linear epitopes are involved in T cell recognition of PLA, independently whether or not subjects are allergic.